Innovations of Sukuk in Global Finance Market: Some Considerations - Mohd. Zain, Nor Razinah; Adeyemi, Adewale Abideen; Engku Ali, Engku Rabiah Adawiah (International Journal of Management and Applied Research, 2019)
Triggered by the progressive development of global Islamic financial services industry, a rapid expansion of Islamic capital market can be detected worldwide. Sukuk as one of sub-components in the Islamic capital market has captured interests from both of issuers and investors. Learning from the experience of conventional bonds, new innovations of sukuk can be traced. In catching up with economic and social factors, innovations of sukuk are progressively done. While sukuk is equipped with Shariah-compliant financing, greater flexibility in its operation and versatile forms of Islamic instruments for investors, some considerations must not be overlooked. This research qualitatively investigates the existence of innovations of sukuk in the global finance market and their importance to the modern societies. Additionally, some considerations in regards to the innovations of sukuk are presented. This research also looks into the best practices of Securities Commission Malaysia (SCM) in coping with the innovations of sukuk. Aiming for the continuous existence of Shariah-compliant in innovations of sukuk, such best practices should be used as examples.